2014
DOI: 10.1016/j.radonc.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences after intensity modulated radiotherapy for head and neck squamous cell carcinoma more likely to originate from regions with high baseline [18F]-FDG uptake

Abstract: Background and Purpose To analyze the recurrence pattern in relation to target volumes and 18F-fluorodeoxyglucose (FDG) uptake on positron emission tomography in head and neck squamous cell carcinoma (HNSCC) patients treated with definitive chemoradiation. Material and Methods 520 patients received radiotherapy for HNSCC from 2005–2009. Among 100 patients achieving complete clinical response and a later recurrence, 39 patients with 48 loco-regional failures had a recurrence CT scan before any salvage therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 17 publications
7
84
2
2
Order By: Relevance
“…Moreover, the delineation of GTV and standardized uptake value (SUV) levels evaluation allows the design of dose escalation strategies, improving the possibility to identify tumor subvolumes with higher risk of recurrences (17,(47)(48)(49)(50). 18 F-FDG PET may be useful even as a prognostic factor due to the ability to early detect tumor recurrences (15)(16)(17)(18)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the delineation of GTV and standardized uptake value (SUV) levels evaluation allows the design of dose escalation strategies, improving the possibility to identify tumor subvolumes with higher risk of recurrences (17,(47)(48)(49)(50). 18 F-FDG PET may be useful even as a prognostic factor due to the ability to early detect tumor recurrences (15)(16)(17)(18)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies allow correlation of imaging features with the patient or tumour outcome (e.g. recurrence location) using follow-up imaging of various lesions [15][16][17][18]. Another imaging approach is to validate the imaging characteristics with biological properties in the surgical specimen [19][20][21][22].…”
Section: Strategymentioning
confidence: 99%
“…Small studies testing temporal stability of hypoxia in NSCLC have so far found inconclusive results. Some studies have observed stable hypoxia [39,40], whereas others have reported a decrease in hypoxia [26,41], or a mix of stable and dynamic hypoxia [42]. Lin et al [43] showed in head and neck cancer that when there is a spatial shift, dose painting of the initial subvolume still results in improved equivalent uniform dose on a later scan.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET imaging is widely used to aid target delineation. Adding this functional imaging modality has shown to improve target definition, over anatomical imaging alone, in several tumour types [42,43].…”
Section: Functional Imaging For Personalized Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation